POSTCOLONIAL CRITIQUE, LITERAL AXIOLOGY, SERBIAN LITERATURE - Vladusić, Slobodan (Porównania, 2015)
This work ana-lyses the relationship between axiological setups of postcolonial critique and virtue criteria set up by modern literature. The essential thesis is that postcolonial studies criticize the virtue crite-ria of modern literature as politically repressive, while at the same time they themselves estab-lish the criterion of political activism as a relevant criterion for valuing the worth of literary work. In conclusion of this work, the analysis is focused on the repercussions of this feature of postcolonial studies and their effect on modern Serbian literature and critique practice. Three conclusions are derived: 1. Serbian literature in order to be accepted within the domain of the postcolonial concept of literature has to become a hybrid literature, thus it has to denounce its national prefix 2. The postcolonial concept is going to initiate a thematic shift within Serbian literature to direction of thematic hybrid situation – affirmation of Megalopolis by newcomers from the countryside 3. The concept of postcolonial literature is going to lead to ideology of literal critics via the phenomenon of critique inquisition: critique that derives from a priori moral inferiority of literal text.